Pembinaan TK-TPA al-Amin Tekait Tata Cara Wudhu dan Shalat di Desa Saotengnga Kecamatan Sinjai Tengah - Mutmainna; Akmal (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2024)
The work program carried out by the author aims to provide an understanding to al-Amin TK/TPA children regarding the procedures for ablution and prayer. This training is carried out for two months and in stages. Where in the first month the author explains the procedures for ablution and in the second month continues to explain the procedures for praying. The results of the work program carried out by the author are that al-Amin's TK/TPA children are able to know how to perform ablution and prayer properly and correctly.